2011
DOI: 10.1007/s10450-011-9375-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydrogen and methane adsorption/separation on silicon nanotubes: a hierarchical multiscale method from quantum mechanics to molecular simulation

Abstract: A combination of ab initio quantum mechanical (QM) calculations and canonical Monte Carlo (CMC) simulations are employed to investigate possible usage of singlewalled silicon nanotubes (SWSiNTs) as a novel media for hydrogen and methane adsorption as well as their separation from each other. By fitting the force field, a Morse potential model is selected as an efficient potential to describe the binding energies between both hydrogen-SiNTs and methane-SiNTs obtained from ab initio calculations. Then CMC simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Recently, several attempts have been made to employ silicon nanotubes as solid phase in analytical separations. However, only a few studies have successfully implemented the hydrogen adsorption on SiNTs. Balilehvand et al investigated the hydrogen and methane adsorption/separation on silicon nanotubes. They found that the capacity of hydrogen adsorption on SiNTs is considerably higher than that on CNTs.…”
Section: Applications In Aqueous Mediamentioning
confidence: 99%
“…Recently, several attempts have been made to employ silicon nanotubes as solid phase in analytical separations. However, only a few studies have successfully implemented the hydrogen adsorption on SiNTs. Balilehvand et al investigated the hydrogen and methane adsorption/separation on silicon nanotubes. They found that the capacity of hydrogen adsorption on SiNTs is considerably higher than that on CNTs.…”
Section: Applications In Aqueous Mediamentioning
confidence: 99%
“…3b). These observations illustrate the responsiveness of the P TDG -probe to short-term changes in downhole Note the different y-axis ranges P TDG , noting that the relatively slower changes in P TDG relative to P BUB may be partly due to methane sorption onto the silicon membrane (Balilehvand et al 2012). They also provide some insight into potential variability in P TDG related to the monitoring set-up.…”
Section: Well F4mentioning
confidence: 70%
“…The effect of pressure on the selectivity of CH 4 over H 2 on SiNTs has displayed the same trend. 117 As mentioned, smaller molecules are more appropriate for packing in the CNT, the selectivity of CH 4 /H 2 decreases with increasing pressure.…”
Section: Monte Carlo Simulationmentioning
confidence: 85%